An uncertain glory India and its contradictions - Dreze, Jean; Sen, Amartya 1933. (Princeton, New Jersey Princeton University Press, 2013)
"When India became independent in 1947 after two centuries of colonial rule, it immediately adopted a firmly democratic political system, with multiple parties, freedom of speech, and extensive political rights. The famines of the British era disappeared, and steady economic growth replaced the economic stagnation of the Raj. The growth of the Indian economy quickened further over the last three decades and became the second fastest among large economies. Despite a recent dip, it is still one of the highest in the world. Maintaining rapid as well as environmentally sustainable growth remains an important and achievable goal for India. In An Uncertain Glory, two of India's leading economists argue that the country's main problems lie in the lack of attention paid to the essential needs of the people, especially of the poor, and often of women. There have been major failures both to foster participatory growth and to make good use of the public resources generated by economic growth to enhance people's living conditions. There is also a continued inadequacy of social services such as schooling and medical care as well as of physical services such as safe water, electricity, drainage, transportation, and sanitation. In the long run, even the feasibility of high economic growth is threatened by the underdevelopment of social and physical infrastructure and the neglect of human capabilities, in contrast with the Asian approach of simultaneous pursuit of economic growth and human development, as pioneered by Japan, South Korea, and China. In a democratic system, which India has great reason to value, addressing these failures requires not only significant policy rethinking by the government, but also a clearer public understanding of the abysmal extent of social and economic deprivations in the country. The deep inequalities in Indian society tend to constrict public discussion, confining it largely to the lives and concerns of the relatively affluent." -- Publisher's description.
A new India? -- Integrating growth and development -- India in comparative perspective -- Accountability and corruption -- The centrality of education -- India's health care crisis -- Poverty and social support -- The grip of inequality -- Democracy, inequality and public reasoning -- The need for impatience.
Keywords: Economic development -- India -- History; India -- Economic conditions -- 1947-.; India -- Social conditions -- 1947-.